Multiscale Entropy Analysis of Health-related Stream Flow Complexity Under Different Human Impacts - Yang, Pan; Yin, Xinan; Tang, Jian (Journal of Environmental Accounting and Management, 2026)
Multiscale entropy (MSE) can effectively measure the streamflow complexity for river health analysis, but the effects of different kinds of human activities on streamflow complexity are still in con- troversy. In response to this question, this study applies the MSE analysis on river flow of three hydrological stations (Huayuankou, Gaocun and Lijin) in the lower Yellow River and the average pre-cipitation and evaporation of 62 meteorological stations across the Yellow River basin. The results indicate that: 1) water consumption could lead to the decrease of streamflow complexity in lower Yel- low River; 2) construction and operation of reservoirs could in-crease the streamflow complexity downstream, and possible expla-nation is the water storage enhanced long range correlation of res- ervoirs; and 3) the intensity of complexity alteration caused by reservoirs is related to both its capacity and position, larger reservoir in upstream has greater impact on streamflow complexity. This study also suggests MSE to be a useful tool in hydrological study and river ecosystem protection in Yellow River.